Google sites Web Development Bioplastic Material and: Transformation of Sciencepreneur Critical and Creative Thinking Skills in Vocational Schools - Emy Nuriyani; Daud Karel Walanda; Sitti Rahmawati; Mery Napitupulu; Darsikin; Syarpin (Universitas Syiah Kuala, 2026)
The main problem in this study is the limited availability of interactive teaching materials and the low cognitive engagement of students in conventional learning environments. This study aims to develop web-based teaching materials using google sites for bioplastics and sciencepreneurship to improve critical and creative thinking skills in vocational high school students. The primary issues underlying this research are the limited availability of interactive teaching materials and students' low cognitive engagement in conventional learning. the research method used was research and development with the addie (analysis, design, development, implementation, and evaluation) development model. The subjects were 30 tenth-grade students in the computer and network engineering program at SMK Negeri 1 Parigi. The research instruments included a validation sheet, a practicality questionnaire, and an essay test to measure critical and creative thinking skills. The results showed that this google sites web-based teaching material was categorized as very feasible, with an average expert validation score of 91.28%. The practicality of the teaching material was assessed as very practical, with an average teacher and student response score of 95.14%. Based on the effectiveness test using the effect size formula (Cohen's d), the experimental class showed a significant increase with a value of 0.841 compared to the control class which was only 0.176 Specifically, the increase in critical thinking skills obtained an effect size value of 0.982 and creative thinking skills of 0.865, both of which are in the high category. Thus, the google sites web-based teaching materials on bioplastics and sciencepreneurs have proven effective in improving students' critical and creative thinking skills.